FISHERMEN’S PERCEPTION OF THE MAJU FISHERMAN VILLAGE (KALAJU) PROGRAM IN PALARAN INDONESIA - Doriana Agata Christi; Fitriyana Fitriyana; Gusti Haqiqiansyah (PT. Jurnal Center Indonesia Publisher, 2026)
This study aims to examine fishermen's perceptions of the Advanced Fishermen's Village Program (KALAJU) in Palaran Indonesia. This study uses a descriptive quantitative approach with purposive sampling technique to select 15 respondents based on specific criteria. The perception indicators used are internal factors, including physiological aspects, interest, attention, unidirectional needs, and emotional conditions. Data analysis was conducted using a Likert scale to measure the fishermen's perception levels toward the program. The research results indicate that fishermen generally have a positive perception of the Advanced Fishermen Village Program across all the indicators used. The cumulative value of the internal factor reached 35.73, which falls into the high category. This indicates that the program was well-received and considered beneficial by the fishermen at the research location. The Maju Fisherman Village Program has strong potential in supporting the improvement of fishermen's welfare. However, sustainable support and effective implementation strategies are needed to maintain and enhance the program's impact.